Preparation method of nitrogen, phosphorus and sulfur triple-doped hollow carbon nanocage material
Through self-assembly and carbonized with CTP and ZIF-8, a hollow nanocarbon cage electrocatalyst with tri-doped nitrogen, phosphorus and sulfur-doped hollow nanocarbon cage electrocatalysts are prepared, which solves the problems of high cost and low catalytic activity of existing ZABs electrocatalysts, and achieves efficient and stable ORR catalytic performance, with good commercial application prospects.
Patent Information
- Application Number
- CN202411619245.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing zinc-air battery (ZABs) cathode oxygen reduction reaction (ORR) electrocatalysts have high cost, low catalytic activity, poor selectivity and poor stability, which limit their commercial development.
By self-assembly and carbonized with covalent triazine polymer (CTP) and ZIF-8, a hollow nanocarbon cage electrocatalyst with nitrogen, phosphorus and sulfur-trioded hollow nanocarbon cage electrocatalyst was prepared, and hexachlorotriphosphazene and bisphenol S were used as phosphorus and sulfur sources to simplify the doping process and reduce costs.
The catalyst exhibits excellent ORR catalytic activity in zinc-air batteries, with half-wave potentials reaching 0.85 V vs. RHE, power density and specific capacity reaching 194 mW cm⁻² and 773 mAh gZn⁻¹, respectively, and exhibits stability over 1000 hours in constant current charge and discharge tests.
Smart Images

Figure CN119627127A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of a nitrogen, phosphorus and sulfur-tri-doped hollow carbon nano cage electrocatalyst, which is applied to the field of green energy storage devices represented by zinc-air batteries. Background Art
[0002] With the rapid development of human society, the global demand for energy continues to rise. Although fossil fuels such as coal, oil and natural gas are still the main energy sources of modern society, their non-renewable nature and environmental pollution have seriously restricted the sustainable development of mankind. Therefore, the development of green sustainable materials and technologies has become a research focus in recent years. In energy conversion and storage technology, metal-air batteries and fuel cells have attracted widespread attention due to their safety, environmental protection, high efficiency and low cost, and have become alternatives to traditional fossil fuels. Among them, the oxygen required for metal-air batteries can be obtained directly from the air. In recent years, researchers have conducted in-depth research on rechargeable zinc-air batteries (ZABs), which have a high theoretical energy density (1353 Wh kg -1 ), and is environmentally friendly, low-cost and safe. However, the cathode oxygen reduction reaction (ORR) of ZABs involves a multi-step electron transfer process, resulting in slow oxygen kinetics; at the same time, the overpotential of the air cathode is large during the charge and discharge cycle, which seriously hinders the practical application of ZABs. At present, commercial ORR electrocatalysts mainly use platinum-based materials, but due to their high cost, scarce resources, poor methanol resistance and single catalytic performance, this has largely limited their large-scale commercial development. Therefore, there is an urgent need to develop electrocatalysts with low cost, high catalytic activity, good selectivity and excellent stability. .
[0003] Carbon nanomaterials have become one of the most attractive materials in the scientific research community due to their low cost, rich structures, good conductivity and excellent thermochemical stability. In the field of ZABs, researchers have significantly improved the ORR catalytic performance of carbon nanomaterials through surface modification, structural reorganization, heteroatom doping and composite methods. In particular, carbon-based materials doped with non-metallic atoms (such as B, F, N, S, and P) can form a unique electronic structure, change the positive charge of adjacent carbon atoms, and provide abundant ORR active centers and high specific surface area, thereby enhancing the electrocatalytic activity of heteroatom-doped carbon nanomaterials. However, the preparation process of most B, F, N, S, and P-doped porous carbon materials often involves complex and harsh process conditions. CTP is regarded as an ideal precursor for the preparation of multi-element co-doped carbon materials due to its excellent thermal stability, simple in-situ heteroatom incorporation method and high specific surface area. In addition to heteroatom doping, nanostructure / morphology design has been proven to be another effective strategy to improve the performance of electrocatalytic materials. Hollow nanostructures have many advantageous properties in green energy storage and conversion, including easily accessible internal space, high specific surface area, and short transmission paths. Template method is a simple method that can effectively construct functional carbon materials with hollow nanostructures. However, the potential of preparing nitrogen-, phosphorus-, and sulfur-doped hollow nanocarbon cage materials by template-induced pyrolysis of covalent triazine polymers (CTPs) as electrocatalytic materials for oxygen reduction reaction (ORR) has not been studied in depth. The present invention has the following significant advantages: (1) Hexachlorotriphosphazene is directly used as a phosphorus source and bisphenol S is used as a sulfur source. Compared with the indirect doping of phosphorus and sulfur atoms during pyrolysis, this in-situ doping method is simpler and more efficient. This method can achieve higher phosphorus and sulfur contents after pyrolysis, thereby effectively reducing costs in industrial applications; (2) ZIF-8 is used as a template agent, and a hollow dodecahedral structure can be formed after self-assembly and carbonization with covalent triazine polymers (CTPs). This specific structure can significantly expose more active sites during the oxygen reduction reaction (ORR), which helps the transport of electrolyte ions and the adsorption and dissociation of intermediates, thereby accelerating the kinetic rate of ORR; (3) Compared with other soft and hard templates, ZIF-8 can be self-removed during the pyrolysis process due to the Cockroach effect, which greatly shortens the process time and improves the synthesis efficiency. Summary of the invention
[0004] The present invention provides a method for preparing a nitrogen, phosphorus and sulfur-tri-doped hollow nano-carbon cage composite material, and the specific steps are as follows: (1) Dissolve zinc nitrate hexahydrate and 2-methylimidazole in methanol solution respectively and stir for 24 h. After the reaction is completed, ZIF-8 powder is obtained. (2) Dissolve ZIF-8 powder, hexachlorotripolyphosphazene and bisphenol S monomers in methanol to obtain a uniform solution, and then mix the two solutions and stir them thoroughly. Subsequently, add a certain amount of N, N-diisopropylethylamine to the stirred solution, and after reaction, a nitrogen, phosphorus and sulfur-tri-doped hollow carbon nanocomposite precursor ZIF-8@PZS powder can be obtained. The product after the reaction needs to be filtered, washed and dried, and the washing solvent can be a conventional washing solvent in the art, such as methanol or water; (3) The ZIF-8@PZS is heated to 800-1000°C in an inert atmosphere and maintained at a constant temperature for pyrolysis; after the pyrolysis reaction is completed, the nitrogen, phosphorus, and sulfur-tri-doped hollow carbon nanocage electrocatalytic material NPS-HCs can be obtained.
[0005] During the pyrolysis process, the temperature is usually raised to 800-1000°C at a heating rate of 5-10°C / min and maintained at a constant temperature for 2-3 hours.
[0006] During the pyrolysis process, a corundum porcelain boat commonly used in the art is used to place the sample in the corundum porcelain boat, and the corundum porcelain boat is placed in the center of the quartz tube. Subsequently, the quartz tube is placed in the center of the tube furnace and vacuumized. At the same time, Ar is continuously introduced into the tube furnace, and finally, it is heated to 800-1000 ° C and maintained at a constant temperature for 2-3 hours. After natural cooling, a hollow carbon nano-electrocatalytic material (NPS-HCs) co-doped with nitrogen, phosphorus and sulfur can be obtained.
[0007] The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole in step (1) is 1:3-4.
[0008] The molar ratio of hexachlorotrimer phosphazene to bisphenol S in step (2) is 1:2-5, wherein bisphenol S needs to be relatively excessive to ensure complete reaction of hexachlorotrimer phosphazene.
[0009] In a preferred embodiment, the inert atmosphere used in step (3) is argon, and its flow rate is set to 50-200 sccm / min. The pyrolysis temperature in step (3) is set to 900°C, and the heating is performed at a heating rate of 5°C / min, and the holding time is 2 hours.
[0010] The present invention designs a nitrogen, phosphorus, and sulfur-tri-doped hollow carbon nanocage electrocatalyst, which has a simple and low-cost synthesis method and exhibits excellent performance and good application effects. 2In the carbon structure, its electronic arrangement is significantly adjusted, thereby effectively enhancing the catalytic activity of the oxygen reduction reaction (ORR). Specifically, the half-wave potential of the catalyst NPS-HC-900 can reach 0.85 V vs. RHE, which exceeds most reported non-metal catalysts and commercial catalysts Pt / C. In addition, the application of NPS-HCs catalysts in zinc-air battery cathode materials shows bright application prospects. The power density and specific capacity of NPS-HC-900 reached 194 mW cm⁻² and 773 mAh gZn⁻¹, respectively, and showed stability of more than 1000 hours in constant current charge and discharge tests. This achievement has laid a solid foundation for the subsequent synthesis of non-metal catalysts, and at the same time provided innovative design ideas for the industry to develop efficient and low-cost catalysts and energy storage materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 The linear voltammetric scan curve (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield) diagram, where (a) alkaline ORR-LSV, (b) N and H2O2 Yield.
[0012] Figure 2 The linear voltammetric scan curve (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield) diagram, where (a) alkaline ORR-LSV, (b) N and H2O2 Yield.
[0013] Figure 3 The linear voltammetric scan curve (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield) diagram, where (a) alkaline ORR-LSV, (b) N and H2O2 Yield.
[0014] Figure 4 The linear voltammetric scan curve (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield) diagram, where (a) alkaline ORR-LSV, (b) N and H2O2 Yield.
[0015] Figure 5 The linear voltammetric scan curve (LSV) and electron transfer number ( N), hydrogen peroxide yield (H2O2 Yield) diagram, where (a) alkaline ORR-LSV, (b) N and H2O2 Yield.
[0016] Figure 6 Cyclic voltammetry curve (CV) and linear voltammetry scan curve (LSV) measured for the sample prepared in Example 6, where (a) is alkaline ORR-CV, and (b) is alkaline ORR-LSV.
[0017] Figure 7 The linear voltammetric scanning curve (LSV) of the sample prepared in Example 1 before and after the test.
[0018] Figure 8 Discharge polarization curves and power density curves of the sample prepared in Example 1 and the commercial catalyst Pt / C.
[0019] Fig. 9 2 and 3 are the discharge polarization curves and power density curves of Example 2 and Example 3.
[0020] Fig.10 The figure shows the rate performance curves of Example 1, Example 2, Example 3 and Pt / C.
[0021] Fig.11 The constant current discharge curves of Example 1, Example 2, Example 3 and Pt / C.
[0022] Fig.12 2 is the cycle performance curve of Example 1 and Pt / C.
[0023] Fig.13 This is a schematic diagram of an electronic photograph of an LED lamp with a lighting voltage of 5 V in Example 1.
[0024] Fig.14 This is the SEM image of Example 1.
[0025] Fig.15 This is the TEM image of Example 1.
[0026] Fig.16 It is a comparison chart of element content and specific surface area of Example 1, Example 2 and Example 3.
[0027] Fig.17 The Raman graphs of Examples 1 to 6 show that characteristic peaks of carbon nanomaterials appear at 1350 cm-1 and 1580 cm-1, and ID / IG describes the degree of defects in the carbon skeleton. DETAILED DESCRIPTION
[0028] Characterization conditions: In the embodiment of the present invention, the test method of ORR is as follows: nitrogen, phosphorus, sulfur-tri-doped hollow carbon nano cage electrocatalyst is used as the working electrode, carbon rod is used as the counter electrode, and Hg / HgO electrode is used as the reference electrode. During the test, the scan rate is set to 10 mV / s, and the alkaline electrolyte used is 0.1 M KOH aqueous solution. Before the test, O 2 The gas was passed into the aqueous solution for half an hour to ensure that the gas reached a natural saturation state. When performing linear sweep voltammetry (LSV) tests, potential (IR) compensation was automatically performed using the Shanghai Chenhua workstation; while in cyclic voltammetry (CV) tests, potential (IR) compensation was not performed.
[0029] Example 1 Zinc nitrate hexahydrate (8 mmol, 2.38 g) and 2-methylimidazole (32 mmol, 2.63 g) were dissolved in 60 mL and 20 mL of methanol solution, respectively, and ultrasonically dispersed until they were uniformly mixed. Then, the two were mixed and stirred for 24 h to obtain ZIF-8 powder. 0.4 g of the above-obtained powder was dissolved in 40 mL of methanol to form solution A, and hexachlorotripolyphosphazene (0.4 mmol, 0.152 g) and bisphenol S (1.3 mmol, 0.325 g) were completely dissolved in methanol (100 mL) to form solution B. Subsequently, solution A was slowly added to solution B and stirred for 1 hour. . Then, 1 mL of N, N-diisopropylethylamine was slowly added dropwise to neutralize the hydrogen chloride generated during the reaction. The stirring reaction continued at room temperature for 8 hours. The product obtained after the reaction was washed three times with methanol and deionized water; then, it was dried in a drying oven overnight to obtain ZIF-8@PZS powder precursor. Set aside. The precursor was placed in a corundum boat, and then the corundum boat was placed in the center of the tube furnace. In an Ar atmosphere, the temperature was raised to 900 °C at a rate of 5 °C / min and maintained for 2 h, and then naturally cooled to room temperature and taken out to finally obtain NPS-HC-900 material.
[0030] Figure 1 The linear sweep voltammetry (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield), where (a) shows the LSV curve of NPS-HC-900 in 0.1 M KOH solution saturated with O2. (b) shows the LSV curve of NPS-HC-900 in 0.1 M KOH solution saturated with O2. N And H2O2Yield curve.
[0031] from Figure 1It can be seen from (a) that the half-wave potential of NPS-HC-900 can reach 0.86 V vs. RHE, and the limiting current density can reach 5.19 mA cm-2.
[0032] from Figure 1 It can be seen from (b) that the electron transfer number of NPS-HC-900 is 4 and the hydrogen peroxide yield is less than 10%, which proves that NPS-HC-900 almost completely undergoes 4e-ORR reaction in O2-saturated 0.1 M KOH solution.
[0033] Example 2 Hexachlorotripolyphosphazene (0.4 mmol, 0.152 g) and bisphenol S (1.3 mmol, 0.325 g) were completely dissolved in methanol (100 mL) to form a uniform dispersion, which was ultrasonicated for 1 h. N,N-diisopropylethylamine (1 mL) was then added to remove the hydrogen chloride generated by the reaction. The stirring reaction continued at room temperature for 8 h, and the obtained product was washed three times with methanol and deionized water; then dried overnight to obtain the PZS powder precursor for use. The precursor was placed in a corundum porcelain boat, and then the corundum porcelain boat was placed in the middle of a tube furnace. The temperature was raised to 900 ℃ at a heating rate of 5 ℃ / min in an Ar atmosphere, and the temperature was kept for 2 h. After natural cooling, the NPS-C-900 material was obtained.
[0034] Figure 2 The linear sweep voltammetry (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield), where (a) shows the LSV curve of NPS-C-900 in 0.1 M KOH solution saturated with O2. (b) shows the LSV curve of NPS-C-900 in 0.1 M KOH solution saturated with O2. N And H2O2Yield curve.
[0035] from Figure 2 It can be seen from (a) that the half-wave potential of NPS-C-900 can reach 0.79 V vs. RHE, and the limiting current density can reach 4.12 mA cm-2.
[0036] from Figure 2 It can be seen from (b) that the electron transfer number of NPS-C-900 is less than 4, and the hydrogen peroxide yield is 10%~30%, which proves that NPS-C-900 mostly undergoes 4e-ORR in O2-saturated 0.1 M KOH solution, and a small part of it undergoes 2e-ORR.
[0037] Example 3 Zinc nitrate hexahydrate (8 mmol, 2.38 g) and 2-methylimidazole (32 mmol, 2.63 g) were dissolved in 60 mL and 20 mL methanol solutions respectively and dispersed evenly by ultrasonication, and then the two were mixed and stirred. The stirring reaction was continued at room temperature for 24 hours, and the obtained product was washed three times with methanol and deionized water; and then dried overnight to obtain the ZIF-8 powder precursor for use. The precursor was placed in a corundum porcelain boat, and then the corundum porcelain boat was placed in the middle of a tube furnace, and the temperature was increased to 900 ℃ at a heating rate of 5 ℃ / min in an Ar atmosphere, and the temperature was kept for 2 hours. After cooling naturally, the NC-900 material was obtained.
[0038] Figure 3 The linear sweep voltammetry (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield), where (a) shows the LSV curve of NC-900 in 0.1 M KOH solution saturated with O2. (b) shows the LSV curve of NC-900 in 0.1 M KOH solution saturated with O2. N And H2O2 Yield curve.
[0039] from Figure 3 It can be seen from (a) that the half-wave potential of NC-900 can reach 0.78 V vs. RHE, and the limiting current density can reach 3.47 mA cm-2.
[0040] from Figure 3 It can be seen from (b) that the electron transfer number of NC-900 is 3~4, and the hydrogen peroxide yield is 20%~60%, which proves that NC-900 mostly undergoes 2e-ORR in O2-saturated 0.1 M KOH solution, and a small part of it undergoes 4e-ORR.
[0041] Example 4 Zinc nitrate hexahydrate (8 mmol, 2.38 g) and 2-methylimidazole (32 mmol, 2.63 g) were dissolved in 60 mL and 20 mL methanol solutions respectively and dispersed uniformly by ultrasonication. Then the two were mixed and stirred for 24 h to obtain ZIF-8 powder. 0.4 g of the above powder was dissolved in 40 mL methanol to form solution A. Hexachlorotripolyphosphazene (0.4 mmol, 0.152 g) and bisphenol S (1.3 mmol, 0.325 g) were completely dissolved in methanol (100 mL) to form solution B. Then solution A was added to solution B and stirred for 1 h. N,N-diisopropylethylamine (1 mL) was added to remove the hydrogen chloride generated by the reaction. The stirring reaction was continued at room temperature for 8 h. The obtained product was washed three times with methanol and deionized water; then dried overnight to obtain the ZIF-8@PZS powder precursor for use. The precursor was placed in a corundum boat, and then the corundum boat was placed in the middle of a tubular furnace. The temperature was increased to 800 °C at a heating rate of 5 °C / min in an Ar atmosphere, and the temperature was kept at that temperature for 2 h. After the temperature was naturally cooled, the NPS-HC-800 material was obtained.
[0042] Figure 4 The linear sweep voltammetry (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield), where (a) shows the LSV curve of NPS-HC-800 in 0.1 M KOH solution saturated with O2. (b) shows the LSV curve of NPS-HC-800 in 0.1 M KOH solution saturated with O2. N And H2O2Yield curve.
[0043] from Figure 4 It can be seen from (a) that the half-wave potential of NPS-HC-800 can reach 0.74 V vs. RHE, and the limiting current density can reach 3.26 mA cm-2.
[0044] from Figure 4 It can be seen from (b) that the electron transfer number of NPS-HC-800 is ~3, and the hydrogen peroxide yield is higher than 50%, proving that NPS-HC-800 undergoes 2e-~4e- ORR in O2-saturated 0.1 M KOH solution.
[0045] Example 5 Zinc nitrate hexahydrate (8 mmol, 2.38 g) and 2-methylimidazole (32 mmol, 2.63 g) were dissolved in 60 mL and 20 mL methanol solutions respectively and dispersed uniformly by ultrasonication. Then the two were mixed and stirred for 24 h to obtain ZIF-8 powder. 0.4 g of the above powder was dissolved in 40 mL methanol to form solution A. Hexachlorotripolyphosphazene (0.4 mmol, 0.152 g) and bisphenol S (1.3 mmol, 0.325 g) were completely dissolved in methanol (100 mL) to form solution B. Then solution A was added to solution B and stirred for 1 h. N,N-diisopropylethylamine (1 mL) was added to remove the hydrogen chloride generated by the reaction. The stirring reaction was continued at room temperature for 8 h. The obtained product was washed three times with methanol and deionized water; then dried overnight to obtain the ZIF-8@PZS powder precursor for use. The precursor was placed in a corundum boat, and then the corundum boat was placed in the middle of a tubular furnace. The temperature was increased to 900 °C at a heating rate of 5 °C / min in an Ar atmosphere, and the temperature was kept at that temperature for 2 h. After the temperature was naturally cooled, the NPS-HC-1000 material was obtained.
[0046] Figure 5 The linear sweep voltammetry (LSV) and electron transfer number ( N ), hydrogen peroxide yield (H2O2 Yield), where (a) shows the LSV curve of NPS-HC-1000 in 0.1 M KOH solution saturated with O2. (b) shows the LSV curve of NPS-HC-1000 in 0.1 M KOH solution saturated with O2. N And H2O2Yield curve.
[0047] from Figure 5 It can be seen from (a) that the half-wave potential of NPS-HC-1000 can reach 0.81 V vs. RHE, and the limiting current density can reach 3.09 mA cm-2.
[0048] from Figure 5 It can be seen from (b) that the electron transfer number of NPS-HC-1000 is ~4, and the hydrogen peroxide yield is ~15%, which proves that NPS-HC-1000 mostly undergoes 4e-ORR in O2-saturated 0.1 M KOH solution, and a small part of it undergoes 2e-ORR.
[0049] Example 6 This section shows the linear sweep voltammetry (LSV) and electron transfer number ( N), hydrogen peroxide yield (H2O2 Yield), where (a) shows the LSV curve of Pt / C in 0.1 M KOH solution saturated with O2. (b) shows the LSV curve of Pt / C in 0.1 M KOH solution saturated with O2. N And H2O2 Yield curve.
[0050] from Figure 6 It can be seen from (a) that the half-wave potential of Pt / C can reach 0.85 V vs. RHE, and the limiting current density can reach 4.93 mA cm-2.
[0051] from Figure 6 It can be seen from (b) that the electron transfer number of Pt / C is 4 and the hydrogen peroxide yield is less than 10%, proving that Pt / C completely undergoes 4e-ORR in O2-saturated 0.1 M KOH solution.
[0052] from Figure 7 It can be seen that after 5000 cycles, the half-wave potential of NPS-HC-900 only decreased by 6 mV, which proves that NPS-HC-900 has strong stability in 0.1 M KOH solution.
[0053] from Figure 8 It can be seen that the power density of NPS-HC-900 can reach 194 mW cm-2, and the power density of Pt / C is 104 mW cm-2. This shows that the performance of the catalyst NPS-HC-900 synthesized by the present invention is better than that of the commercial catalyst Pt / C, which provides convenience for subsequent industrial development.
[0054] from Fig. 9 It can be seen that the power densities of NPS-C-900 and NC-900 are 42 mW cm-2 and 35 mW cm-2, respectively. This indicates that the optimal carbonization temperature is 900 °C, and both too low and too high temperatures are not conducive to their application in zinc-air batteries.
[0055] from Fig.10 It can be seen that NPS-HC-900, Pt / C, NPS-C-900 and NC-900 all have good rate performance. NPS-HC-900 has a higher discharge voltage under the same conditions, proving that NPS-HC-900 can show superiority in zinc-air battery applications.
[0056] from Fig.11It can be seen that the specific capacities of NPS-HC-900, NPS-C-900, NC-900 and commercial catalyst Pt / C are 773 mAh gZn-1, 576 mAh gZn-1, 528 mAh gZn-1 and 738 mAh gZn-1, respectively. It can be proved that the constant current discharge performance of NPS-HC-900 is better than that of other control samples.
[0057] from Fig.12 It can be seen that the constant current charge and discharge times of NPS-HC-900 and commercial catalyst Pt / C+IrO2 are 1100 h and 135 h, respectively. This proves the excellent cycle performance and stable performance of NPS-HC-900 in zinc-air battery applications.
[0058] from Fig.13 It can be seen that NPS-HC-900 is practically applied in zinc-air battery electrode materials.
[0059] from Fig.14 It can be seen that the structure of NPS-HC-900 is a hollow dodecahedron, which can expose more active sites, promote the penetration of electrolyte, and help increase the ORR rate.
[0060] from Fig.15 It can be seen that NPS-HC-900 is a hollow nanostructure with a large specific surface area, which is conducive to the transmission of electrons and electrolyte ions and kinetically improves the ORR rate.
[0061] from Fig.16 From the figure, we can see the content and specific surface area of each element in NPS-HC-900, NPS-C-900 and NC-900, among which the specific surface area of NPS-HC-900 can reach 1240 m2 g-1. This proves that NPS-HC-900 can expose more active sites, which is conducive to the occurrence of ORR.
[0062] from Fig.17 It can be seen that NPS-HC-800, NPS-HC-900, NPS-HC-1000, NPS-C-900 and NC-900 have characteristic peaks of carbon nanomaterials at 1350 cm-1 and 1580 cm-1. ID / IG describes the degree of defects in the carbon skeleton. The ID / IG of NPS-HC-800, NPS-HC-900, NPS-HC-1000, NPS-C-900 and NC-900 are 1.27, 1.10, 1.06, 1.04 and 0.98 respectively. As the carbonization temperature increases, their degree of defects decreases. This is because the higher the temperature, the more complete the graphitization.
[0063] Table 1 Summary of ORR performance parameters of example samples and control samples.
[0064]
[0065] Table 2 Summary of performance parameters of ZABs of example samples and Pt / C.
[0066]
Claims
1. A method for preparing nitrogen, phosphorus and sulfur-tri-doped hollow carbon nanocage material, characterized in that: The specific preparation method is: (1) Dissolve zinc nitrate hexahydrate and 2-methylimidazole in methanol respectively and stir evenly to form a ZIF-8 structure; (2) The obtained ZIF-8 powder, hexachlorotriphosphazene and bisphenol S monomer were dissolved in methanol respectively, uniformly dispersed and mixed, and N, N-diisopropylethylamine was added as an initiator. After the reaction, the mixture was filtered, washed and dried to obtain the precursor ZIF-8@PZS; (3) Finally, ZIF-8@PZS was heated to 800-1000 °C in an inert atmosphere and maintained at this temperature to complete the pyrolysis process, and finally the nitrogen, phosphorus, and sulfur-tri-doped hollow carbon nanocage electrocatalytic material NPS-HCs was obtained.
2. The method for preparing the nitrogen, phosphorus and sulfur-tri-doped hollow carbon nanocage electrocatalyst according to claim 1, characterized in that: The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole in step (1) is 1:3-4.
3. The method for preparing the nitrogen, phosphorus and sulfur-tri-doped hollow carbon nanocage electrocatalyst according to claim 1, characterized in that: The molar ratio of hexachlorotripolyphosphazene to bisphenol S in step (2) is 1:2-5.
4. The method for preparing the nitrogen, phosphorus and sulfur-tri-doped hollow carbon nanocage electrocatalyst according to claim 1, characterized in that: The inert atmosphere in step (3) is argon, and the flow rate is controlled between 50-200 sccm.
5. Application of nitrogen, phosphorus and sulfur-tri-doped hollow carbon nano cage electrocatalyst prepared by the method according to any one of claims 1 to 4, wherein the NPS-HCs nanomaterial is applied to the air cathode material of zinc-air batteries.
6. An air cathode material for a zinc-air battery, characterized in that The invention comprises a nitrogen, phosphorus and sulfur-tri-doped hollow carbon nanocage electrocatalyst prepared by the method according to any one of claims 1 to 4.
Citation Information
Cited By
Electroplating solution for high-tungsten-content hydrogen sulfide corrosion-resistant sleeve coating and preparation process of electroplating solution
CN120738717A